PENGARUH KOMPETENSI PROFESIONAL DAN MOTIVASI KERJA TERHADAP KINERJA YANG DIMODERASI GAYA KEPEMIMPINAN TRANSFORMASIONAL (Studi Empiris pada Guru SMA Negeri 1,2,3,4 dan 5 Kota Semarang) - Maryusis, Maryusis; Susilowati, Yeye (Jurnal Ilmiah Telaah Manajemen, 2017)
This research aimed to examine the Influence of professional competence and work motivation on the teachers performances of superior public senior high school in Semarang city with transformational leadership style as moderaration variable. The population of this study are 186 teachers, sampling techniques in this study is proportional random sampling methode. The method used in this research is regression with intereaction quasi moderation. This study is explanatory research. Measurements used a Likert scale of five alternative answers. Test instruments used are validity and reliability, while the normality test used Kolmogorov-Smirnov statistics. Heteroskedastisitas test used Glejser method, test model used is F test (Goodness of fit) and the coefficients of determination (Adjusted R square), while hypotesis test used regression analysis with t-test at the 0,05 significance level.. The results of this study are: (1) the professional competence has positive and significant effect on teacher performance, (2) the work motivation has positive and significant effect on teacher performance 3) Transformational leadership style doesn’t have effect on the teacher performance, (4) Transformational leadership style doestn’t moderate influenced professional competence on the teacher performances (5) Transformational leaadership style doesn’t moderate influence Work motivation on the teacher performances. Keywords: professional competence, work motivation, transformational leadership style, teacher performance.